Estimasi Pengembangan Perangkat Lunak Dengan Use Case Size Point - Puguh Jayadi; Juwari; Muh.Nur Luthfi Azis; Kelik Sussolaikah (Bulletin of Information Technology (BIT), 2022)
In software development activities one of the stages that need to be known by the project manager and the client is the estimated effort. The estimation activity is used as a reference in determining the time and personnel involved in software development. There are several methods used in software estimation such as Function Point, COCOMO, and Use Case Point. However, there are still some shortcomings such as the subjective tendency to measure complexity and lack of calculation on technical factors and environmental factors. The estimation used in this study uses the Use Case Size Point method which is the development of the Use Case Point method. The results of the Use Case size Point were used to provide a more accurate evaluation of effort with 0.01 Mean Magnitude of Relative Error (MMRE) and 0.01 Mean Magnitude of Relative Error (MMER)